Neural correlates of audiovisual temporal processing – Comparison of temporal order and simultaneity judgments. (6th August 2015) - Binder, M.
Highlights: Simultaneity and temporal order judgment tasks assess temporal processing of stimuli. The two tasks were compared in a blocked-design fMRI study with audiovisual pairs. Both tasks activated the bilateral attentional fronto-parietal network. Activation in left frontal, parietal and temporo-occipital regions was observed for temporal order judgments. Simultaneity judgments did not reveal any additional activation. Abstract: Multisensory integration is one of the essential features of perception. Though the processing of spatial information is an important clue to understand its mechanisms, a complete knowledge cannot be achieved without taking into account the processing of temporal information. Simultaneity judgments (SJs) and temporal order judgments (TOJs) are the two most widely used procedures for explicit estimation of temporal relations between sensory stimuli. Behavioral studies suggest that both tasks recruit different sets of cognitive operations. On the other hand, empirical evidence related to their neuronal underpinnings is still scarce, especially with regard to multisensory stimulation. The aim of the current fMRI study was to explore neural correlates of both tasks using paradigm with audiovisual stimuli. Fifteen subjects performed TOJ and SJ tasks grouped in 18-second blocks. Subjects were asked to estimate onset synchrony or temporal order of onsets of non-semantic auditory and visual stimuli. Common areas of activation elicited by both tasks were found in the bilateral fronto-parietal network, including regions whose activity can be also observed in tasks involving spatial selective attention. This can be regarded as an evidence for the hypothesis that tasks involving selection based on temporal information engage the similar regions as the attentional tasks based on spatial information. The direct contrast between the SJ task and the TOJ task did not reveal any regions showing stronger activity for SJ task than in TOJ task. The reverse contrast revealed a number of left hemisphere regions which were more active during the TOJ task than the SJ task. They were found in the prefrontal cortex, the parietal lobules (superior and inferior) and in the occipito-temporal regions. These results suggest that the TOJ task requires recruitment of additional cognitive operations in comparison to SJ task. They are probably associated with forming representations of stimuli as separate and temporally ordered sensory events.